Quantitation of pregabalin by HPLC-UV method using ninhydrin derivatization: development and validation - Mutalabisin, Fathiy; Helal Uddin, A.B.M.; Sengupta, Pinaki; Mohamed, Farahidah; Chatterjee, Bappaditya (Bentham Science Publishers, 2021)
Introduction: A simple and reliable high performance liquid chromatographic method has been developed for the quantitative determination of pregabalin in bulk and dosage form. Pregabalin, a γ amino butyric acid analogue, has negligible sensitivity to UV or fluorescence detection. Hence, it has been derivatized by ninhydrin to form a chromophoric complex that could be quantified by UV detec-tion. Materials and Methods: The concentration of ninhydrin was set to 5 mg/ml and a phosphate buffer solution (pH 7.4) was used as a solvent for the reaction. The resultant complex was separated by HPLC and detected by a UV detector at 569nm wavelength. Results: The developed method showed a linear response within 50 to 600 µg/mL of pregabalin. The method was accurate with mean recovery values within 100 ± 2%. The repeatability of the method was established by intra-day and inter-day precision study. Finally, a commercial pregabalin capsule was assayed by the developed HPLC method including ninhydrin derivatization. The result of the mean assay was found to be 100.37 ±2.94 %. Conclusion: This is the first time we are reporting pregabalin analysis using ninhydrin derivatization for HPLC analysis. Therefore, the developed method can be considered as a significant improvement in pregabalin quantitation and it can be easily applied for routine quality control tests of pregabalin. © 2020 Bentham Science Publishers.